Типи семантичних зв’язків у медичних текстах - Заяць, Антоніна; Романюк, Андрій (Видавництво Львівської політехніки, 2014)
This article is dedicated to semantic relations types in medical textdata in context of the relation extraction process and further development of the relation extraction system for the Ukrainian language.
Keywords: екстракція семантичних зв’язків; опрацювання природної мови; семантичні сутності; схема розмітки